2021
DOI: 10.1158/1055-9965.epi-20-1803
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking and Estrogen-Related Cancer

Abstract: Cigarette smoking is a known cause of many cancers, yet epidemiological studies have found protective associations with the risk of four "estrogen-related" malignancies: endometrial cancer, endometrioid and clear cell ovarian cancers, and thyroid cancer. This review considers epidemiological and biological aspects of these associations, focusing particularly on estrogen signaling, and contrasts them with those for breast cancer, another estrogen-related malignancy. The observational findings regarding the inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 184 publications
1
7
1
2
Order By: Relevance
“…Conversely, ndings from three large-scale cohort investigations indicate an inverse relationship between the duration of post-menopausal smoking and breast cancer risk, contrasting with a tendency towards increased risk in premenopausal smoker. This pattern mirrors observations in endometrial cancer, wherein post-menopausal smoking, but not premenopausal smoking, is associated with diminished risks [54] . Currently, there exists a paucity of studies pertaining to the association between smoking and breast pathologies, necessitating further investigation to elucidate the nexus between smoking and breast diseases.…”
Section: Discussionsupporting
confidence: 82%
“…Conversely, ndings from three large-scale cohort investigations indicate an inverse relationship between the duration of post-menopausal smoking and breast cancer risk, contrasting with a tendency towards increased risk in premenopausal smoker. This pattern mirrors observations in endometrial cancer, wherein post-menopausal smoking, but not premenopausal smoking, is associated with diminished risks [54] . Currently, there exists a paucity of studies pertaining to the association between smoking and breast pathologies, necessitating further investigation to elucidate the nexus between smoking and breast diseases.…”
Section: Discussionsupporting
confidence: 82%
“…Considering that age is a substantial risk factor for endometrial cancer, therefore, SNP rs7128029 G>A could synergize with age to exacerbate the increased risk of endometrial cancer [ 28 ]. In addition, unhealthy lifestyle presents another risk factors for increasing the predisposition to endometrial cancer [ 29 ]. Consistently, we found that the rs7128029 G>A-endometrial cancer association was more pronounced in the population who are smoker.…”
Section: Discussionmentioning
confidence: 99%
“…6 Concerning the modifiable cancer risk factors shown in the present study, blood estrogen levels can be elevated in postmenopausal women with obesity 7 and in pre-and postmenopausal women with drinking habits, 8,9 but cannot be elevated in women with smoking habits. 10 The age-specific incidence and mortality rates of uterine body cancer, another estrogen-related cancer, also increased from 2005 to 2015, despite smaller rates compared with those of breast cancer. The age-specific incidence rate of uterine body cancer increased in a bell-shaped pattern, which was, interestingly, almost the same as that of breast cancer in 1980.…”
Section: Discussionmentioning
confidence: 99%
“…6 Concerning the modifiable cancer risk factors shown in the present study, blood estrogen levels can be elevated in postmenopausal women with obesity 7 and in pre- and postmenopausal women with drinking habits, 8,9 but cannot be elevated in women with smoking habits. 10…”
Section: Discussionmentioning
confidence: 99%